2022
DOI: 10.3201/eid2806.220158
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Attack Rate, Transmission and Incubation Periods, and Serial Interval of SARS-CoV-2 Omicron Variant, Spain

Abstract: a total of 622 cases of SARS-CoV-2 infection compatible with the Omicron variant (BA.1/B.1.1.529) (1) were studied by the Contact Tracing Programe in Cantabria, Spain. A total of 1,420 close contacts (household, social, and occupational) were identified; 455 secondary cases were identified. We report the main epidemiologic characteristics of these cases, such as secondary attack rate (SAR), transmission period, incubation period, and serial interval, and compared these characteristics with those for Delta vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 6 publications
7
57
0
Order By: Relevance
“…The HSAR of COVID-19 was 31.8% (95% CI 27.7-36.2) during the omicron variantdominant period in Itako, Japan. The HSAR for the omicron variant was 25% in Norway [8], 49% in Spain [9], 53% in the USA [10], and 65% in Korea [11]. The HSAR in the present study was in the range of those reported previously.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The HSAR of COVID-19 was 31.8% (95% CI 27.7-36.2) during the omicron variantdominant period in Itako, Japan. The HSAR for the omicron variant was 25% in Norway [8], 49% in Spain [9], 53% in the USA [10], and 65% in Korea [11]. The HSAR in the present study was in the range of those reported previously.…”
Section: Discussionsupporting
confidence: 73%
“…Studying the transmissibility of the Omicron variant and comparing it with that of the Delta variant is useful. However, few studies have reported the HSAR of the omicron SARS-CoV-2 variant [8][9][10][11][12]. The effective reproduction number of omicron is greater than that of delta in several countries [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 541 studies underwent full-text review. Eight studies [ 19 , 21 , 32 , 33 , 34 , 41 , 42 , 43 ] with information concerning the percentage of asymptomatic infections among SARS-CoV-2 Omicron variant-positive individuals were included in the final analysis ( Figure 1 ). The characteristics of the studies included in this systematic review and meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… The Percentage of Asymptomatic Infections Among SARS-CoV-2 Omicron Variant-Positive Individuals [ 19 , 21 , 32 , 33 , 34 , 41 , 42 , 43 ]. …”
Section: Figurementioning
confidence: 99%
“…Spain has been one of the European countries with the highest number of COVID-19 cases, according to the European Centre for Disease Prevention and Control (ECDC, (accessed on 22 January 2022)). Previous studies have analyzed the epidemiology of SARS-CoV-2 in Spain [ 5 , 112 ], certain Spanish cities or AC [ 113 , 114 , 115 , 116 , 117 , 118 ], and variants [ 119 , 120 ]. However, as far as we know, this is the first study including all SARS-CoV-2 GISAID available sequences from the 17 AC and 2 Autonomous Cities since the beginning of the pandemic until the sixth epidemiologic wave, including the most prevalent mutations.…”
Section: Discussionmentioning
confidence: 99%